STRATEGI PEMASARAN BERBASIS MARKETING MIX DALAM MENSTABILKAN KONTINUITAS PELANGGAN PADA UMKM LANCAR JAYA WALLETCRAFT - Awaliya Franciska, Cahya; Munawaroh, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the marketing mix based strategies used to stabilize customer continuity at Lancar Jaya Walletcraft. The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. Informants consisted of the business owner and several wholesale customers. Findings indicate that the marketing mix plays a crucial role in maintaining customer continuity: product strategies emphasize customization, material quality, neat stitching, and quality control. pricing is set based on production costs with adjustments to remain competitive, distribution operates through business-to-business relations and personal selling, promotion is conducted via WhatsApp and supported by after-sales service. The study concludes that consistent application of the marketing mix, supported by product quality consistency and strong customer relationships, enhances customer satisfaction and encourages sustainable repeat purchases.